Treating patients with platinum-sensitive extensive-stage small-cell lung cancer in a real-world setting - Sands, Jacob; Subramanian, Janakiraman (Frontiers in Oncology, 2023)
Extensive-stage small-cell lung cancer (ES-SCLC) is an aggressive disease with poor 5-year survival. The first-line standard-of-care for ES-SCLC is platinum plus etoposide, along with 1 of the immune checkpoint inhibitors atezolizumab or durvalumab. Although SCLC first-line therapy often leads to rapid responses, treatment becomes more challenging at progression, particularly for those with a chemotherapy-free interval (CTFI) of ≤6 months. The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines®) for SCLC no longer specify treatment recommendations in this setting, but options approved by the US Food and Drug Administration include topotecan and lurbinectedin. Participation in a clinical trial is recommended as an option regardless of CTFI. Other NCCN-recommended regimens are paclitaxel, irinotecan, temozolomide, and cyclophosphamide/doxorubicin/vincristine, among others. Nivolumab and pembrolizumab are options in those not previously treated with a checkpoint inhibitor. For patients with platinum-sensitive SCLC (CTFI >6 months), preferred treatment per the NCCN Guidelines® for SCLC is retreatment with platinum and etoposide, although the use of immune checkpoint inhibitors is discouraged if there is progression on a drug in this class. Further research on immunotherapies and combination regimens is ongoing, and continuing work on the subcharacterization of SCLC may lead to better precision of therapies that promote more durable responses in individual patients with ES-SCLC.